In silico design and screening of hypothetical MOF-74 analogs and their experimental synthesis. Issue 9 (28th June 2016) - Witman, Matthew; Ling, Sanliang; Anderson, Samantha; Tong, Lianheng; Stylianou, Kyriakos C.; Slater, Ben; Smit, Berend; Haranczyk, Maciej
Abstract : We present the in silico design of MOFs exhibiting 1-dimensional rod topologies by enumerating MOF-74-type analogs based on the PubChem Compounds database. We simulate the adsorption behavior of CO2 in the generated analogs and experimentally validate a novel MOF-74 analog, Mg2 (olsalazine). Abstract : In this work we present the in silico design of metal-organic frameworks (MOFs) exhibiting 1-dimensional rod topologies. We introduce an algorithm for construction of this family of MOF topologies, and illustrate its application for enumerating MOF-74-type analogs. Furthermore, we perform a broad search for new linkers that satisfy the topological requirements of MOF-74 and consider the largest database of known chemical space for organic compounds, the PubChem database. Our in silico crystal assembly, when combined with dispersion-corrected density functional theory (DFT) calculations, is demonstrated to generate a hypothetical library of open-metal site containing MOF-74 analogs in the 1-D rod topology from which we can simulate the adsorption behavior of CO2 . We finally conclude that these hypothetical structures have synthesizable potential through computational identification and experimental validation of a novel MOF-74 analog, Mg2 (olsalazine).